Upaya Pencegahan dan Penularan Scabies di Pondok Pesantren Ibrohimiyyah Demak melalui Edukasi Personal Hyegiene pada Santri - Yuzza Alfarra; Pasid Harlisa; Hesti Wahyuningsih Karyadini (Indonesian Journal of Community Services, 2022)
Ibrohimiyyah Islamic Boarding School (“Ponpes”) is located in Brumbung RT 05 RW 04 Mranggen Demak. The density of occupancy in each room at the Ponpes causes low personal hygiene and environmental sanitation at the place. Our community service activity (Pengabdian masyrakat/PkM) was aimed to solve the problem of (1)The lack of understanding of the students (“stantri”) about the importance of personal hygiene in preventing many diseases, especially the transmission of scabies, (2) The lack of knowledge of Ponpes administrators and santri about scabies and how to prevent transmission, (3) The number of students who currently suffer from scabies and have not been handled properly who can resulting in the transmission of this disease in the cottage environment so that it affects the rest time and productivity of students. Our PkM provided health education through counseling about scabies disease, its causes, ways to prevent transmission and how to treat wounds caused by scabies to santri and Ponpes administrators. Examination of the severity of scabies was done to determine the scabies. To prevent the spreading of the disease to others, the santri with scabies was also treated by topical scabicide, namely Permethrin cream 5% or ointment 2-4, or oral Ivermectin. Education, examination and treatment of scabies in santri was useful for increasing santri' knowledge so that they are able to understand personal hygiene in preventing many diseases, especially the transmission of scabies. Santri are able to understand about scabies and how to prevent its transmission.